Reduced proximal tubular expression of protein endocytic receptors in proteinuria is associated with urinary receptor shedding. Issue 6 (23rd November 2017) - Fatah, Hiwa; Benfaed, Nura; Chana, Ravinder S; Chunara, Mohamed H; Barratt, Jonathan; Baines, Richard J; Brunskill, Nigel J
ABSTRACT: Background: Filtered proteins, including albumin, are reabsorbed in the proximal tubule (PT) mediated by megalin, cubilin and the neonatal Fc receptor (FcRn). Proteinuria is an important renal biomarker linked to poor prognosis but expression of these key receptors is not well studied. Methods: Megalin expression was determined at protein and messenger RNA (mRNA) levels in kidneys from proteinuric patients, and the expression of megalin, cubilin and FcRn was examined in the kidneys of mice with protein-overload proteinuria. The presence of receptors in the urine of proteinuric and control mice was also studied. Results: In nephrotic patients, megalin expression is reduced while mRNA is increased. In proteinuric mice megalin, cubilin and the neonatal FcRn protein are all reduced in PTs. Megalin and FcRn mRNA are increased in proteinuric mice, whereas that for cubilin was reduced. In proteinuric mice increased urinary excretion of each of these endocytic receptors was observed. Conclusions: It is concluded that in proteinuria, expression of all the key protein re-absorptive receptors is significantly reduced in the PT in association with increased turnover and urinary shedding.